(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Scar site endometriosis is a rare event. It mostly occurs after obstetrics and gynaecological related surgeries. Classical presentation is cyclical pain and swelling at or near scar in relation to menstrual cycle. A case of scar site endometriosis in a 25-year-old female is presented. Patient developed characteristic clinical features 3 years after cesarean section. Clinical diagnosis was supported by ultrasonography. A wide excision with clear margins was curative. High index of clinical suspicion and wide excision remain the keys to successful management.